Force-modulated reductive elimination from platinum(ii) diaryl complexes. Issue 33 (26th July 2021) - Yu, Yichen; Wang, Chenxu; Wang, Liqi; Sun, Cai-Li; Boulatov, Roman; Widenhoefer, Ross A.; Craig, Stephen L.
Abstract : The influence of mechanical force on the rates of model reductive elimination reactions depends on the structure of the force-transducing ligand and provides a measure of geometry changes upon reaching the transition state. Abstract : Coupled mechanical forces are known to drive a range of covalent chemical reactions, but the effect of mechanical force applied to a spectator ligand on transition metal reactivity is relatively unexplored. Here we quantify the rate of C(sp 2 )–C(sp 2 ) reductive elimination from platinum(ii ) diaryl complexes containing macrocyclic bis(phosphine) ligands as a function of mechanical force applied to these ligands. DFT computations reveal complex dependence of mechanochemical kinetics on the structure of the force-transducing ligand. We validated experimentally the computational finding for the most sensitive of the ligand designs, based on MeOBiphep, by coupling it to a macrocyclic force probe ligand. Consistent with the computations, compressive forces decreased the rate of reductive elimination whereas extension forces increased the rate relative to the strain-free MeOBiphep complex with a 3.4-fold change in rate over a ∼290 pN range of restoring forces. The calculated natural bite angle of the free macrocyclic ligand changes with force, but 31 P NMR analysis and calculations strongly suggest no significant force-induced perturbation of ground state geometry within the first coordination sphere of the (P–P)PtAr2 complexes. Rather, the force/rate behavior observed across this range of forces is attributed to the coupling of force to the elongation of the O⋯O distance in the transition state for reductive elimination. The results suggest opportunities to experimentally map geometry changes associated with reactions in transition metal complexes and potential strategies for force-modulated catalysis.